Komunikasi Antarbudaya dalam Masyarakat Multikultural di Era Digital - Ilham Mushariawan (Al-Qolamuna: Journal Komunikasi dan Penyiaran Islam, 2026)
Intercultural communication is the interaction process that occurs between individuals or groups with different cultural backgrounds in a multicultural society. The diversity of cultures, ethnicities, religions, languages, and customs within a society can both be a social asset and pose challenges to the communication process if not accompanied by an attitude of tolerance and mutual understanding. This study aims to analyze the role of intercultural communication in building harmonious social relations in a multicultural society and to identify factors that support and hinder intercultural communication in social life. This study used a descriptive method with a qualitative approach. Data collection techniques included observation, interviews, and documentation. Research informants included community leaders, religious leaders, educators, youth, and members of the general public involved in intercultural social interactions. Data analysis used the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and conclusion drawing. The results indicate that intercultural communication plays a crucial role in creating tolerance, strengthening social integration, and fostering mutual respect among culturally diverse groups. Supporting factors for intercultural communication include openness, empathy, tolerance, and understanding of other cultural values, while inhibiting factors include language differences, stereotypes, social prejudice, and a lack of cultural understanding. Thus, intercultural communication is a crucial tool in creating a harmonious, peaceful, and respectful multicultural society amidst cultural diversity. Abstrak Komunikasi antarbudaya merupakan proses interaksi yang terjadi antara individu atau kelompok yang memiliki latar belakang budaya berbeda dalam kehidupan masyarakat multikultural. Keberagaman budaya, suku, agama, bahasa, dan adat istiadat dalam masyarakat dapat menjadi kekayaan sosial sekaligus menimbulkan tantangan dalam proses komunikasi apabila tidak disertai sikap toleransi dan saling memahami. Penelitian ini bertujuan untuk menganalisis peran komunikasi antarbudaya dalam membangun hubungan sosial yang harmonis di tengah masyarakat multikultural, serta mengidentifikasi faktor pendukung dan penghambat komunikasi antarbudaya dalam kehidupan sosial masyarakat. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi. Informan penelitian terdiri atas tokoh masyarakat, tokoh agama, pendidik, pemuda, dan masyarakat umum yang terlibat dalam interaksi sosial antarbudaya. Teknik analisis data menggunakan model analisis interaktif Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa komunikasi antarbudaya memiliki peranan penting dalam menciptakan toleransi, memperkuat integrasi sosial, serta membangun sikap saling menghargai antar kelompok masyarakat yang berbeda budaya. Faktor pendukung komunikasi antarbudaya meliputi sikap terbuka, empati, toleransi, dan pemahaman terhadap nilai budaya lain, sedangkan faktor penghambatnya meliputi perbedaan bahasa, stereotip, prasangka sosial, dan kurangnya pemahaman budaya. Dengan demikian, komunikasi antarbudaya menjadi sarana penting dalam menciptakan kehidupan masyarakat multikultural yang harmonis, damai, dan saling menghormati di tengah keberagaman budaya.